PENDAMPINGAN PEMBUATAN NOMOR INDUK BERUSAHA (NIB) SEBAGAI UPAYA PENINGKATAN LEGALITAS UMKM “CELLO CAKE & BAKERY” DI KELURAHAN BENOWO, SURABAYA - Prasetyo Pambudhi, Kukuh; Dermawan, Rizky (Gapenas Publisher, 2024)
Business Identification Number (NIB) is the identity of a business actor, whether business entity, individual business or business entity, which is issued by Online Single Submission (OSS). Meanwhile, the micro and small business permit, hereinafter abbreviated as (IUMK), is a one-sheet letter in the form of a micro-small business permit. This has not yet been applied to the